Kelayakan Mahasiswa sebagai Subjek Penyulih dalam Penelitian Perilaku dengan Metode Eksperimen: Sebuah Reviu Literatur: (The Feasibility of Students as Surrogates in Behavioral Research Using Experimental Methods: A Literature Review) - Suryaningrum, Diah Hari; Utama, I Wayan Wisnu (PT Global Digital Sains Tekno, 2023)
This study investigates the feasibility of using students as surrogates in behavior research. Using students as surrogates for accounting practitioners, auditors, or managers has been a controversial issue for decades that can lead to underutilizing experimental methods, such as neglecting the randomization in sample selection. This study relies on reviewing and analyzing the literature on the students' surrogate debate in experimental research, especially in the management and accounting fields. In behavioral research using the experiment method, it is important to select students as surrogates for the study, increase external validity, and the reality of research instruments. This literature review finds that students may or may not be adequate surrogates for non-students in many decision-making experiments. The adequacy of students as surrogates depends on several issues. First, students’ selection as surrogates should be performed cautiously, depending on the context of the cases. Second, the decision-making process is a contingency approach. Lastly, the characteristics of students should resemble the targeted population. ABSTRAK: Penelitian ini menyelidiki kelayakan menggunakan mahasiswa sebagai subjek penyulih atau pengganti dalam penelitian perilaku. Menggunakan mahasiswa sebagai penyulih praktisi akuntansi, auditor, atau manajer telah menjadi isu kontroversial selama beberapa dekade yang dapat menyebabkan kurangnya pemanfaatan metode eksperimental, seperti mengabaikan pengacakan dalam pemilihan sampel. Penelitian ini mengandalkan tinjauan dan analisis literatur tentang debat penyulih mahasiswa dalam penelitian eksperimental, khususnya di bidang manajemen dan akuntansi. Dalam penelitian behavioral yang menggunakan metode eksperimen, penting untuk memilih mahasiswa sebagai penyulih penelitian, meningkatkan validitas eksternal, dan realitas instrumen penelitian. Tinjauan literatur ini menemukan bahwa mahasiswa mungkin atau mungkin tidak menjadi penyulih yang memadai bagi non-mahasiswa dalam banyak eksperimen pengambilan keputusan. Kecukupan mahasiswa sebagai penyulih tergantung pada beberapa masalah. Pertama, pemilihan mahasiswa sebagai penyulih harus dilakukan secara hati-hati, tergantung pada konteks kasusnya. Kedua, proses pengambilan keputusan adalah pendekatan kontingensi. Terakhir, karakteristik mahasiswa harus menyerupai populasi sasaran.